Bee Pollen as Functional Food: Insights into Its Composition and Therapeutic Properties - Asmae El Ghouizi; Meryem Bakour; Hassan Laaroussi; Driss Ousaaid; Naoual El Menyiy; Christophe Hano; Badiaa Lyoussi (MDPI AG, 2023)
Bee pollen is a hive product made up of flower pollen grains, nectar, and bee salivary secretions that beekeepers can collect without damaging the hive. Bee pollen, also called bee-collected pollen, contains a wide range of nutritious elements, including proteins, carbs, lipids, and dietary fibers, as well as bioactive micronutrients including vitamins, minerals, phenolic, and volatile compounds. Because of this composition of high quality, this product has been gaining prominence as a functional food, and studies have been conducted to show and establish its therapeutic potential for medical and food applications. In this context, this work aimed to provide a meticulous summary of the most relevant data about bee pollen, its composition-especially the phenolic compounds-and its biological and/or therapeutic properties as well as the involved molecular pathways.